Various Methodologies of Hadith Research (Sanad Research, Matan, Study of Figures and Living Hadith) - Syauqi Alif Attar; Engkos Kosasih; Muhammad Al Mighwar (al-Afkar, Journal For Islamic Studies, 2025)
Research has three basic objectives, namely discovery, proof, and development. The purpose of discovery means discovering a theory or new understandings of hadith, the purpose of proof means research that focuses on eliminating doubts that exist in a hadith, and the purpose of development means the expansion of a figure's theory about hadith. Through this article, the author will discuss a variety of hadith research methodologies, this paper uses a qualitative research writing method with a literature approach, The author discusses four famous hadith research methodologies, namely sanad hadith research, matan hadith research, figure study research and living hadith research. The sanad research is the genealogy of the narrators who transform the matan from the main source. Matan research is in the form of maintenance, definition, interpretation and maintenance of the values that exist in the redaction of hadith. Character study research describes how a certain figure thinks about the hadith, whether it is a view that comes from Muslim intellectuals or orientalists. While living hadith research means research on the interaction, understanding and practices of people in certain areas towards hadith.